MEDAN MAKNA MAKANAN TRADISIONAL DALAM BAHASA MELAYU DALEK SUKADANA - Fitaliya, Fitaliya; Simanjuntak, Hotma; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is focused on the field of meaning of traditional food in the Malay language of Sukadana dialect. Based on data analysis found 64 data classified by genus or class in the form of staple foods, snack foods and side dishes. Based on the results of an analysis of the field of meaning of traditional food in the Sukadana dialect Malay, there are 64 traditional food lexemes in the Sukadana dialect Malay. Based on the types of traditional food lexical meanings in Malay Dilaek Sukadana 64 data are obtained from lexical meaning in the name of food, 65 lexical meanings in the form of materials, 19 lexical meanings in the form of food tools, 14 lexical meanings in the form or process of making food, 16 lexical meanings in the form of food, 12 lexical meaning in the form of food color. The semantic function of leksem has their respective functions, namely as a staple food, snacks, and side dishes. 4) Implication of procedure text, that is, how to make food related to Indonesian language learning in the 2013 curriculum in class VII SMP KD (3.5). regional specialties, etc.) and various sources that are read and heard. Keywords:Field of meaning, Sukadana Dialect, Traditional food